Heterogeneous Ni- and Cd-Bearing Ferrihydrite Precipitation and Recrystallization on Quartz under Acidic pH Condition - Chong Dai; Lin, Mingxi; Yandi* Hu (ACS Earth and Space Chemistry, 2017)
Ferrihydrite, as one of the most common naturally occurring iron oxides, can sequester toxic metals through co-precipitation. In this study, using grazing-incidence small-angle X-ray scattering, the heterogeneous precipitation of pure, Ni-, and Cd-bearing ferrihydrite on quartz was quantified in 0.1 mM Fe3+ solutions in the absence and presence of 1 mM Ni2+ or Cd2+ (pH 3.8 ± 0.1). Under acidic condition, the limited hydrolysis of metal ions resulted in their small amounts of incorporation in ferrihydrite lattices (<0.1%), several orders of magnitude lower than those reported at neutral and alkaline pH conditions. The presence of Ni2+ or Cd2+ did not significantly affect the surface charges of either ferrihydrite pre-nucleation clusters (PNCs) or quartz surfaces. Therefore, with similar electrostatic interactions between PNCs and quartz, similar initial heterogeneous precipitation rates of pure and Ni- and Cd-bearing ferrihydrite on quartz were observed. Later on, continuous heterogeneous nucleation and growth of ferrihydrite nanoparticles resulted in their increased polydispersity, and the size-dependent solubility of ferrihydrite nanoparticles caused the Ostwald ripening process. The presence of Ni and Cd was found to retard the recrystallization of ferrihydrite, probably as a result of their structural incorporation, which could inhibit the dissolution of ferrihydrite. This study provided new kinetic and mechanistic insights for understanding the effects of metal ions on the heterogeneous precipitation and recrystallization processes of ferrihydrite nanoparticles on mineral surfaces, which can better predict the fate and transport of heavy metals.